SANITATION AND HYGIENE COMPLIANCE AND ASSOCIATED FACTORS AMONG FOOD HANDLERS IN SOME SECONDARY SCHOOLS IN MINNA METROPOLIS, NIGER STATE, NIGERIA. - P.O. ONYIA; S.B. KAZE; A.O. OPASOLA; H.O. SAWYERR (African Journal of Health, Safety and Environment, 2026)
Unsafe food handling in schools can expose students to microbial contamination and foodborne illness. This study assessed sanitation and hygiene compliance and associated factors among food handlers in some secondary schools in Minna Metropolis, Niger State, Nigeria. A descriptive cross-sectional analytical study was conducted in 20 public and private secondary schools. Questionnaires (125) were administered, out of which 122 were completed, giving a response rate of 97.6%. Microbiological assessment included 120 hand-swab samples and 100 ready-to-eat food samples. Data were collected using a structured questionnaire, a 12-item observational checklist and microbiological procedures. Respondents were predominantly female (96.7%), aged 26–35 years (44.3%) and educated to secondary level (54.1%). Viable bacterial growth was detected in 80.8% of hand swabs and 85.0% of food samples. Isolates included Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Enterococcus faecalis. Good knowledge was recorded among 36.1% of respondents, 49.2% had positive attitudes, while 59.0% demonstrated average or poor hygiene practices. Compliance with every observed hygiene practice was below 50%. Educational level (χ² = 7.784, df = 1, p = 0.005), knowledge level (χ² = 11.818, df = 1, p < 0.001) and attitude (χ² = 7.445, df = 1, p = 0.006) were significantly associated with compliance. The findings reveal substantial microbial contamination and a gap between food-safety knowledge and practice. Practical training, adequate handwashing facilities, routine inspection and microbiological surveillance are recommended.